A proposed relationship between management practices and safety performance in the oil and gas industry in Iraq - Khdair, Wameedh A.; Mohd Shamsudin, Faridahwati; Subramaniam, Chandrakantan (2011)
Occupational accidents occur are either due to lack of knowledge, training, lack of supervision, and lack of rules implementation. In addition, a human error leads to negligence, carelessness of workers, recklessness of workers and lack of monitoring and controlling.The rapid growth in the industry globally has raised concern on safety and health issues at the workplace. As a result more occupational accidents and injuries at workplace make headline news all over the globe. The aim of this paper is to review related empirical literatures and highlight the need to investigate safety performance with respect to the oil and gas industry in Iraq.This paper discusses the role of management practices that may have an impact on safety performance in the oil and gas industry.Toward the end of the paper, a conceptual model depicting the relationships between management practices and safety performance will be offered.